2000
DOI: 10.1128/aem.66.7.3052-3057.2000
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Halophilic Bacteria in Crystallizer Ponds from Solar Salterns

Abstract: It is generally assumed that hypersaline environments with sodium chloride concentrations close to saturation are dominated by halophilic members of the domain Archaea, while Bacteria are not considered to be relevant in this kind of environment. Here, we report the high abundance and growth of a new group of hitherto-uncultured Bacteria in crystallizer ponds (salinity, from 30 to 37%) from multipond solar salterns. In the present study, these Bacteria constituted from 5 to 25% of the total prokaryotic communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
178
6
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 309 publications
(196 citation statements)
references
References 41 publications
9
178
6
3
Order By: Relevance
“…Numbers of Bacteria and total cell counts showed a negative dependence with salinity, while Archaea was rather independent of this variable (Supplementary Tables S12 and S13). This may seem contradictory with previous results (Guixa-Boixereu et al, 1996;Antó n et al, 2000;Pedró s-Alió , 2005) that indicated that archaeal numbers increased with salinity. This discrepancy Figure 3 Temporal variation of total counts (grey symbols), Archaea (white symbols) and Bacteria (black symbols) in the different ponds.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…Numbers of Bacteria and total cell counts showed a negative dependence with salinity, while Archaea was rather independent of this variable (Supplementary Tables S12 and S13). This may seem contradictory with previous results (Guixa-Boixereu et al, 1996;Antó n et al, 2000;Pedró s-Alió , 2005) that indicated that archaeal numbers increased with salinity. This discrepancy Figure 3 Temporal variation of total counts (grey symbols), Archaea (white symbols) and Bacteria (black symbols) in the different ponds.…”
Section: Resultscontrasting
confidence: 56%
“…Prokaryotic community dynamics and their relation to environmental parameters Total microbial counts were in the range previously observed in solar salterns (Guixa-Boixereu et al, 1996;Antó n et al 1999Antó n et al , 2000Benlloch et al 2002;Oren, 2002;Estrada et al, 2004;Burns et al, 2007;Mutlu et al 2008;Eulloumi et al, 2009) ranging from 6.3 Â 10 6 to 4.79 Â 10 7 cells ml À 1 in CR30 (OC) and CCAB (JL), respectively (Figure 3). Although throughout the concentration process from seawater to saturated brines there is an overall increase of cell density, at concentrations 420% this trend is not always observed (Guixa-Boixereu et al, 1996;Boujelben et al, 2012), as shown here.…”
Section: Resultsmentioning
confidence: 77%
“…The domination of Firmicutes in PS is not in agreement with the opinion that Bacteroidetes is the most abundant bacterial phylum in clone libraries from crystallizer ponds [25,26]. According to Ant on et al [8], the presence of different bacterial taxa in them could be due either to their import from previous ponds with lower salinity or to their active growth in the crystallizers. The high number of the clones affiliated with this phylum suggested their active growth in PS.…”
Section: Salt Composition Of Watermentioning
confidence: 47%
“…The uncultured Bacteroidetes lineage has been reported to comprise 69% of all bacterial 16S rRNA clones from Pond 11 in Guerrero Negro salterns [22] and 50% in the Chula Vista salterns [32]. Although Salinibacter has been found ubiquitously in numerous hypersaline environments [8,34], it was not identified in either PS or in Maras salterns [21]. Abundance of new Bacteroidetes groups, different from Salinibacter, in the salterns has been established by single-cell genome analyses [35].…”
Section: Salt Composition Of Watermentioning
confidence: 99%
See 1 more Smart Citation